The counter-revolution of science : - Hayek, F. A. (Liberty Press, 1979)
The Counter-Revolution of Science: Studies on the Abuse of Reason is a 1952 book by Nobel laureate economist Friedrich Hayek, in which the author addresses the problem of scientism in the social sciences, where researchers and reporters attempt to apply the methods and claims of objective certainty from hard science, despite the fact that these attempt to eliminate the human factor from study, yet these "soft" sciences center around attempting to understand human action